'An elder in punk clothes': purged frets and finding true mugham in post-Soviet Azerbaijan. Issue 2 (4th May 2018) - Dessiatnitchenko, Polina
ABSTRACT: Today one encounters a striking diversity of approaches when it comes to the arrangement of scalar intervals on the tar, Azerbaijan's primary national instrument. Frets are moved, added, omitted according to the idiosyncrasies of each musician. Each tonal scheme is fervently defended and justified by various factors such as aesthetic taste, a putative knowledge of pre-Soviet mugham, the desire to highlight an 'Eastern' nature of mugham, 'mission from above', and even suggested contact with the dead. What once was a rigid structure during Soviet times has now become flexible, unhinged from the past by the experimentation, innovation, restoration and reconstitution of musicians. Through an analysis of this extended creative moment, I theorise the many attempts to reintroduce extra frets as nativism. Instead of trying to find a pattern or argue for which version is historically valid, I stress the importance of all attempts as forms of decolonial activity.